ISG15 mRNA transcript level in circulating leucocytes prognostic of overall survival in hepatocellular carcinoma patients and correlated with quality of life disturbances involved in anorexia-cachexia - Li, Leung; Tang, Nelson L. S.; Mo, Frankie; Koh, Jane; Hui, Edwin P.; Ma, Brigette; Chan, Stephen L.; Lee, Kit F.; Yu, Simon C. H.; Yeo, Winnie (Frontiers in Oncology, 2025)
BackgroundAn increasing number of immuno-therapeutic agents have proven efficacy in hepatocellular carcinoma (HCC). Inflammatory markers (c-reactive protein, interleukin-8 and inflammatory score) have been found to be prognostic factors in HCC patients. These inflammatory markers have demonstrated correlations with quality of life (QOL) disturbances in fatigue, appetite loss and nutritional concern. Type I interferon response triggered by HCC could be responsible for an inflammatory state and anorexia-cachexia syndrome leading to these specific QOL impairment. Peripheral blood Interferon Stimulated Gene 15 (ISG15) messenger ribonucleic acid (mRNA) transcript level, a biomarker for type I interferon response, was evaluated for its prognostic significance for overall survival (OS) in a prospective cohort of HCC patients. QOL measurement was employed to systemically capture and quantify patients’ clinical manifestations for correlations with ISG15 mRNA transcript level.MethodsClinical, QOL and laboratory data of 340 treatment naïve HCC patients were collected at study entry. ISG15 mRNA transcript levels in circulating leucocytes were quantified. Independent prognostic factors for OS were identified. Correlation analyses between ISG15 mRNA transcript level and scores of QOL factors were performed.ResultsHigh ISG15 mRNA transcript level in circulating leucocytes was an independent prognostic factor for poor OS (hazard ratio 1.62 [1.23-2.15]; p-value<0.01). The median OS of patients with high ISG15 gene expression was significantly shorter than those with low expression, 4.7 versus 14.3 months respectively (p-value<0.03). There were significant correlations between high ISG15 mRNA transcript level and worse scores in QLQ-C30 fatigue, appetite loss and QLQ-HCC18 nutritional disturbances (p-values <0.05).ConclusionsElevated ISG15 mRNA transcript level in peripheral blood leucocytes was an independent poor prognostic factor for OS in HCC patients. Patients with higher ISG15 gene expression, suggesting more intense type I interferon response, had significantly worse OS. High ISG15 gene expression demonstrated significant correlations with QOL disturbances in fatigue, appetite loss and nutritional concern. These QOL factors could be capturing the anorexia-cachexia manifestations from interferon response induced by HCC.